Relire Gaston Bachelard today - Perru, Olivier (2017)
This paper considers three aspects of the thought of Bachelard with the aim of an education in the scientific thought: some epistemological obstacles more frequently met in education as the obstacle of common experience and the obstacle of false general information (La formation de l’esprit scientifique, 1938); the way the scientific reasoning concerns the whole experimental approach and effort of theorization (Le racionalism appliqué, 1949); the complementarities between the scientific process and the literary, artistic or philosophic process in the approach of nature. In this last prospect, it is convenient to present the surrounding nature as a set of realities to be approached under diverse looks: scientific, artistic, philosophic, poetic…